Complete genome sequence of Dehalobacter restrictus PER-K23T. Issue 3 (May 2013) - Kruse, Thomas; Maillard, Julien; Goodwin, Lynne; Woyke, Tanja; Teshima, Hazuki; Bruce, David; Detter, Chris; Tapia, Roxanne; Han, Cliff; Huntemann, Marcel; Wei, Chia-Lin; Han, James; et al.
Abstract Dehalobacter restrictus strain PER-K23 (DSM 9455) is the type strain of the speciesDehalobacter restrictus .D. restrictus strain PER-K23 grows by organohalide respiration, coupling the oxidation of H2 to the reductive dechlorination of tetra- or trichloroethene. Growth has not been observed with any other electron donor or acceptor, nor has fermentative growth been shown. Here we introduce the first full genome of a pure culture within the genusDehalobacter . The 2, 943, 336 bp long genome contains 2, 826 protein coding and 82 RNA genes, including 5 16S rRNA genes. Interestingly, the genome contains 25 predicted reductive dehalogenase genes, the majority of which appear to be full length. The reductive dehalogenase genes are mainly located in two clusters, suggesting a much larger potential for organohalide respiration than previously anticipated.